Research agendas of female and male academics: a new perspective on gender disparities in academia - Santos, J. M. (2020)
The presence of gender disparities in academia was assessed by analysing the characteristics of the research agendas of academics. Multivariate analysis of variance and structural equation modelling coupled with multi-group analysis were used to identify different gender trajectories. The research agenda preferences of women were less risky and less focused on fields likely to lead to scientific discovery, but were organised in a more collaborative way than those of men. In addition, institutional characteristics were found to influence the research agenda preferences of both women and men. However, the perceived autonomy allowed by a university was more important for female than for male academics to develop more ambitious, collaborative, risky and multidisciplinary efforts. Female academics also needed more time after completing their PhD to develop a preference for riskier research agendas, but past research outputs, the number of co-authors and mobility did not change their agendas.